Development of High School Students' Mathematical Reasoning Ability Instruments on Three Dimension Material - Siti Qomariyah; Rani Darmayanti (Universitas PGRI Madiun, 2023)
The purpose of this study was to develop an evaluation tool for learning mathematics to measure the mathematical reasoning abilities of high school students. The type of development applied is related to the model developed by Thiagarajan. The study population consists of four schools in Pasuruan City. The sample of this research was class XII SMA YALC Pasuruan. Data collection techniques used mathematical reasoning instruments about three-dimensional material consisting of three descriptive questions. Data analysis uses validity, reliability, discriminatory power and difficulty. The results of this study indicate that the assessment tool measures the mathematical reasoning abilities of high school students which are well developed and feasible so that they can be used.